Development and integration of human-AI interactions in service applications: Conceptual framework and review - Nick Tugarin; Christian van Husen (International Journal of Information Management Data Insights)
The rapid advancement of AI technologies has created opportunities and challenges across industries, particularly in service sectors where human interaction is crucial. This study systematically reviews the literature on human-AI interaction in service applications, aiming to understand how these interactions can be effectively designed, economically viable, and human-centered. A systematic literature review covering publications from 2015 to 2024 was conducted, following a structured search protocol that resulted in 90 selected articles. The review identifies key dimensions and interconnected elements of human-AI interaction, which are synthesized into a conceptual framework. This framework outlines the fundamental relationships between these dimensions and provides practical implications for the service industry and directions for future research. Furthermore, real-world application examples illustrate how these findings can be translated into practice. They demonstrate adaptability across different service domains and their potential to inspire innovative, scalable, and human-centric AI solutions.